TEACHING WRITTEN ANNOUNCEMENT THROUGH GALLERY WALK TECHNIQUE (An Experimental Study of Eighth Grade Students at SMP Muhammadiyah 1 Weleri, Kabupaten Kendal, in the Academic Year of 2013/2014) (ELT Forum: Journal of English Language Teaching, 2014)
The objective of this study was to find out whether there was significant difference in the achievement of writing announcement text between the eighth grade students of SMP Muhammadiyah 1 Weleri in the academic year of 2013/2014 who were taught by using Gallery Walk technique and those who were taught by using conventional method. To meet this objective, an experimental research design called pretest-posttest control group design was applied. The research was carried out at SMP Muhammadiyah 1 Weleri. The subjects of the research were two classes. The experimental group was the students of VIII-A which consisted of 28 students and was taught by using Gallery Walk technique. The control group was the students of VIII-B which consisted of 28 students and was taught by using conventional method. The data of the research were obtained from the writing test on pre-test and post-test. Based on the pre-test analysis, the value of tvalue was 0.38, while the value of ttable was 1.67. Since the value of tvalue was lower than the ttable, it meant that there was no significant difference in the students’ achievement of writing announcement text between experimental and control groups on pre-test. Meanwhile, based on the post-test analysis, the value of tvalue was 1.76. Compared with the value of ttable, 1.67, the tvalue was higher than the ttable. It meant that there was significant difference in the students’ achievement of writing announcement text after the treatment was given where the students’ achievement in experimental group was higher or better than the control group. The result above indicates that the use of Gallery Walk technique in teaching writing announcement text brought about significant improvement.